1999
DOI: 10.1088/0953-8984/11/16/008
|View full text |Cite
|
Sign up to set email alerts
|

Deep gap states of a single vacancy in cubic SiC

Abstract: The character of relaxation of atoms around a vacancy in cubic silicon carbide is determined with the help of the empirical potential of Tersoff. The recursion method of Haydock and Nex is applied to calculate the density of states derived from atoms situated around the defect. The outward relaxation of the lattice surrounding a empty site is established. The lattice relaxation results in the shift of gap states toward the conduction band. Vacancy levels of carbon at 0.5 eV and silicon at 0.45 and 1.98 eV are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…For comparison, the energetic intervalmin in 3C-SiC is 7.2, 5.1 and 3.7 eV according to experiment [34], our data and Robertson's calculation [34], respectively. Our scheme gives the C and Si dangling bond states in 3C-SiC at about 0.4 and 2.1 eV (above the VB top), which is very close to our previous findings (0.5 and 1.98 eV) [35] and the recent data [39] (0.38 and 2.15 eV). A single vacancy in c-Si and diamond gives rise to gap levels at 0.3 and 1.55 eV, correspondingly.…”
Section: Computational Aspectssupporting
confidence: 91%
See 1 more Smart Citation
“…For comparison, the energetic intervalmin in 3C-SiC is 7.2, 5.1 and 3.7 eV according to experiment [34], our data and Robertson's calculation [34], respectively. Our scheme gives the C and Si dangling bond states in 3C-SiC at about 0.4 and 2.1 eV (above the VB top), which is very close to our previous findings (0.5 and 1.98 eV) [35] and the recent data [39] (0.38 and 2.15 eV). A single vacancy in c-Si and diamond gives rise to gap levels at 0.3 and 1.55 eV, correspondingly.…”
Section: Computational Aspectssupporting
confidence: 91%
“…In the RM calculations, the initial cell was spread to a large cluster of 4096 atoms conformable to periodic conditions. The DOS of silicon carbide was accurately constructed using the approach of Nex [25], retaining 54 levels of recursion coefficients [35]. The comparison of the DOSs obtained in the framework of the three mentioned methods has showed that these procedures give similar results.…”
Section: Computational Aspectsmentioning
confidence: 99%
“…Using a large-cluster recursion method with Slater-Koster parametrization, Li and Lin-Chung [18] have found that C and Si vacancies in β-SiC would behave as acceptors and donors, respectively. However, in later papers, where the ab initio pseudopotential method within the supercell approach [19], the tight-binding Green-function method [20], the LMTO Green-function method [21], and the recursion method [22] were used, an opposite behaviour of vacancy states has been reported. In the quoted works, except [19,22], the effects of the lattice relaxation on the local electronic structure were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, electron beam energy in our experiment is relatively low, therefore the 1.97 eV peak is manifested only as a weak shoulder on the background of the band-to--band emission at 2.38 eV. The situation with purified nanowires is quite different and this allows us to make a conclusion that produced nanowires of 3C silicon carbide are defects enriched, providing a larger number of D 1 irradiative centers [18]. Relatively broad measured CL band with respect to reported sharp photoluminescence lines [9] can be explained assuming that emission peak might shift slightly depending on the size of 1D nanostructures while the collected CL spectrum represents an integral contribution.…”
Section: Resultsmentioning
confidence: 70%